Inhibition of JNK ameliorates depressive-like behaviors and reduces the activation of pro-inflammatory cytokines and the phosphorylation of glucocorticoid receptors at serine 246 induced by neuroinflammation. (March 2020) - Zhang, Juntao; Lin, Wenjuan; Tang, Mingming; Zhao, Yawei; Zhang, Ke; Wang, Xiaqing; Li, Yingcong
Highlights: Neuroinflammation induced depressive-like behavior. Neuroinflammation upregulated the JNK phosphorylation in three brain areas. Neuroinflammation upregulated the phosphorylation of GR-Ser 246 . Inhibition of JNK ameliorated neuroinflammation-induced depressive-like behavior. Inhibition of JNK reduced neuroinflammation and phosphorylation of GR-Ser 246 . Abstract: Depression is associated with immune dysregulation and the aberrant activity of the hypothalamic-pituitary-adrenal (HPA) axis. However, the neurobiological molecular mechanisms underlying these associations remain unclear. c-Jun amino-terminal kinase (JNK), an important modulator in inflammation and stress responses, is often critically implicated in the development of central nervous system diseases. However, whether and how JNK mediates neuroinflammation-induced depression remains largely unknown. In this study, we investigated the role of JNK in depressive-like behaviors induced by central lipopolysaccharide (LPS) infusion. The results showed that LPS infusion led to depressive-like behaviors, accompanied by increased proinflammatory cytokine expression, increased JNK activation, and upregulated glucocorticoid receptor (GR) phosphorylation at serine 246 (pGR-Ser 246 ) in the habenula (Hb), amygdala (Amyg) and medial prefrontal cortex (mPFC). Treatment with SP600125, a known JNK inhibitor, prevented the LPS-induced hyper-activation of JNK and alleviated depressive-like behaviors. Moreover, LPS-induced increases in the expression levels of TNF-α, IL-1β and pGR-Ser 246 in these brain regions were reduced when the rats were treated with SP600125. Our results show, for the first time, that JNK activities in the Hb, Amyg, and mPFC are involved in the modulation of neuroinflammation-induced depression and participate in the regulation of the expression of proinflammatory cytokines and GR phosphorylation, which are pathological factors associated with depression. Our findings provide new insights into the mechanism of neuroinflammation-associated depression and suggest that the JNK pathway may be a potential target for treating inflammation-related depression.